(untitled) - Ludwig, John A. (New York, 1988)
An accessible introduction to quantitative methods in community ecology, with related software. Provides a thoughtful overview on the nature of data collection, followed by detailed explanations of the major statistical techniques applied to problems in population dynamics. Presents important conclusions about the use (and abuse) of specific techniques. Examples include communities of both flora and fauna, prey-predator relations, the effects of food supply on populations, and species abundance and overlap models. Software includes several BASIC microcomputer programs which can be used with the examples provided or with other data sets.
Thống kê ứng dụng- Kỹ thuật Môi trường
Keywords: Ecology; Statistical methods